Assessing Transgender and Gender Nonconforming Asylum Claims: Towards a Transgender Studies Framework for Particular Social Group and Persecution - Avgeri, Mariza (Frontiers in Human Dynamics, 2021)
Abstract In this article, I focus on gender identity and gender expression as grounds for international protection. After clarifying issues of terminology and theoretical framework, namely Transgender Studies, I criticize the current framework for determining membership in a Particular Social Group (PSG) for the purposes of the Refugee Convention, drawing on Berg and Millbank’s work on the concept of self-identification and gender non-conformity as a means to assess transgender asylum claims (2013). I problematize the issues arising in the assessment of well-founded fear of persecution and the form it may take in transgender and gender nonconforming asylum claims. Drawing connections between sexuality and gender identity/expression claims, I attempt to provide a humanizing and depathologized framework for assessing the credibility of transgender and gender nonconforming applicants. Finally, by critiquing the work of Hathaway and Pobjoy (2012) and drawing from current human rights norms, I reflect on how to make good law with transgender cases without reproducing medicalized notions of gender identity or placing all the burden of proof on the applicants. In so doing, this article attempts to achieve a balance between theoretical and practical challenges that arise in the Refugee Status Determination (RSD) process involving transgender and gender nonconforming applicants. This article serves as an attempt to critically review the existing scholarship within the framework of transgender studies and offers insights for a refined framework of refugee status determination based on an inclusive reading of Particular Social Group and persecution drawing on the reading of crucial case law from anglophone countries.